Northern Ireland and the European Union : The dynamics of a changing relationship - Murphy, Mary C. (Book collections on Project MUSE., 2014)
This unique study breaks new ground in engaging the study of Northern Ireland politics directly with broader debates about European integration and European governance. The text offers comprehensive coverage of the institutional development of Northern Ireland following the UK government's devolution programme and Northern Ireland's development as an autonomous policy actor in Europe.